Ang Pagpapahalagang moral at ispiritwal sa relasyong pangkapwa mula sa pilosopikal na pananaw (1991)
This paper explains the historical origins and the nature of two major components of values education: the moral and the spiritual. The author highlights the humanitarian theory of moral ethics and analyzes the seven fundamental and supreme criteria of the moral and binding relationship between the moral and spiritual.
Keywords: Social skills -- Education; Moral education; Education -- Social aspects